THE SIX ARROWS OF ATATÜRKISM, WITH SPECIAL REFERENCE TO THE EQUAL RIGHTS OF WOMEN - Perger, Adam (Faculty of Law Sriwijaya University, 2023)
Mustafa Kemal AtatÃ¼rk was one of the greatest, if not the greatest, figures in Turkish history, and he did not earn this title without reason. The reforms and innovations he brought to Turkey brought about real change in theory and natural social and political terms. One of the most striking manifestations of these reforms was the so-called 'six arrows' system, which effectively summed up AtatÃ¼rk's political essence and ideas. In this paper, I will describe the elements of the 'six arrows' system, examining their social and political implications, particularly the steps taken to achieve women's equality. I have chosen impact analysis as the research method, as I considered it appropriate in the context of women's emancipation, given the many social impacts of introducing new legislation in Turkish society. In my thesis, I have greatly emphasized the historical overview of the right to marry freely - primarily from a legal-historical perspective- to obtain a genuinely complex picture of the six arrows system as manifested in law practice. In choosing the research method, I proceeded from the assumption that the various disciplines and applied sciences now make it possible to predict the expected consequences of legislative decisions with varying degrees of reliability, and to examine the results of decisions already taken after the event, comparing the facts with the anticipated effects. Suppose we accept that the purpose of legislation is to produce some consequence. In that case, an impact assessment is a prominent tool for assessing the effectiveness and efficiency of individual legislative products and the legislative process.